2014
DOI: 10.5194/angeo-32-1415-2014
|View full text |Cite
|
Sign up to set email alerts
|

Deterministic prediction of surface wind speed variations

Abstract: Abstract. Accurate prediction of wind speed is an important aspect of various tasks related to wind energy management such as wind turbine predictive control and wind power scheduling. The most typical characteristic of wind speed data is its persistent temporal variations. Most of the techniques reported in the literature for prediction of wind speed and power are based on statistical methods or probabilistic distribution of wind speed data. In this paper we demonstrate that deterministic forecasting methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…But in reality, wind is highly unsteady and to compute the actual load, an unsteady BEM is required. 11,31 Since the wind velocity is a function of both space and time, it is important to know the position of the blade at any instant with respect to a fixed inertial coordinate system. This inertial coordinate system is placed at the bottom of the tower.…”
Section: Computation Of Actual Aerodynamic Loadmentioning
confidence: 99%
See 2 more Smart Citations
“…But in reality, wind is highly unsteady and to compute the actual load, an unsteady BEM is required. 11,31 Since the wind velocity is a function of both space and time, it is important to know the position of the blade at any instant with respect to a fixed inertial coordinate system. This inertial coordinate system is placed at the bottom of the tower.…”
Section: Computation Of Actual Aerodynamic Loadmentioning
confidence: 99%
“…whereṼ 1 is the wind velocity with respect to the ground andṼ 0 is the wind velocity with respect to the rotor,ã 34 ;ã 23 ;ã 12 are the transformation matrices to transform the velocity from ground to rotor frame of reference. 11,31 Figure 5 shows the different coordinate systems used with respect to which the velocities are referred. The relative velocity with respect to the rotor can be found as (Figure 6)…”
Section: Computation Of Actual Aerodynamic Loadmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has recently been demonstrated that the underlying dynamics of apparent random-like fluctuations of wind speed measurements is deterministic, low-dimensional and chaotic. 4,5,6 Hybrid models have been developed recently by combining different methods such as physical, statistical and machine learning methods to enhance prediction accuracy. 7,8 Models based on artificial neural network and other data learning techniques have also been gaining increased attention in literature in the recent past.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from these traditional methods, it has been recently reported that apparent random oscillation of wind speed data is chaotic, suggesting non-linear deterministic prediction schemes can be used for accurate short-term predictions [13]. In our previous work we have analysed the scope of deterministic methods to predict wind speed variations, and demonstrated that these methods are capable of providing reasonably accurate predictions up to a few hours [14].…”
Section: Introductionmentioning
confidence: 99%